Efficiency of N2 Gas Flushing Compared to the Lactoperoxidase System at Controlling Bacterial Growth in Bovine Raw Milk Stored at Mild Temperatures - Munsch-Alatossava, Patricia; Quintyn, Romanie; De Man, Ingrid; Alatossava, Tapani; Gauchi, Jean-Pierrre (Frontiers in Microbiology, 2016)
To prevent excessive bacterial growth in raw milk, the FAO recommends two options: either cold storage or activation of the lactoperoxidase system (LPs/ HT) in milk with the addition of two chemical preservatives, hydrogen peroxide (H) and thiocyanate (T). N2 gas flushing of raw milk has shown great potential to control bacterial growth in a temperature range of 6 to 12°C without promoting undesired side effects. Here, the effect of N2 gas (N) was tested as a single treatment and in combination with the lactoperoxidase system (NHT) on seven raw milk samples stored at 15 or 25°C. For the ratio defined as bacterial counts from a certain treatment/counts on the corresponding control, a classical Analyse of Variance (ANOVA) was performed, followed by mean comparison with the Ryan-Einot-Gabriel-Welsch multiple range test (REGWQ). Altogether, the growth inhibition was slightly but significantly higher at 25°C than at 15°C. Except for one sample, all ratios were lower for HT than for N alone; however, these differences were not judged to be significant for five samples by the REGWQ test; in the remaining two samples, N was more effective than HT in one case and less effective in the other case. This study shows that N2 gas flushing, which inhibited bacterial growth in raw milk at 15 and 25°C for 24 and 12 h, respectively, could constitute an alternative to LPs where no cold storage facilities exist, especially as a replacement for adulterating substances.